THE ROLE OF INTERNATIONAL LAW IN PROMOTING GLOBAL ISLAMIC ECONOMIC BALANCE: CHALLENGES AND OPPORTUNITIES IN OIC COUNTRIES - Adinugraha, Hendri Hermawan; Achmad Tubagus Surur; Rizky Andrean (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This research aims to comprehensively investigate the preparation for implementing mandatory halal regulations for food and beverage products in Indonesia. This research also examines the role of international law in promoting the balance of the Islamic global economy in member countries of the Organization of Islamic Cooperation. This research employs a normative legal research method, utilizing a statutory approach. The primary legal materials used include the 1945 Constitution of the Republic of Indonesia, Law No. 23 of 1992, Law No. 7 of 1996, Law No. 6 of 1967, Law No. 8 of 1999, Law No. 33 of 2014, Government Regulation No. 31 of 2019, and Law No. 39 of 2021. Data collection techniques used literature studies, and data analysis was carried out using qualitative descriptive methods. The results showed that the regulation of mandatory halal certification for food and beverage products in Indonesia is regulated in Law Number 33 of 2014, Government Regulation Number 31 of 2019, and Law Number 39 of 2021. Preparation for the implementation of this mandatory halal regulation is a legal requirement to ensure peace and comfort for the public when consuming or using halal products. This study also found that, when implemented appropriately, international legal policies can foster Islamic economic growth in OIC countries. Some countries, such as Malaysia and Turkey, have successfully adopted and enforced international law, thereby improving banking stability and attracting foreign investment. This study concludes that Law No. 33/2014 guarantees the availability of halal products, and the government is obligated to foster and supervise the guarantee of halal products. On October 17, 2024, the first phase of halal obligation for food products, beverages, slaughter services, and slaughter products will be enforced throughout Indonesia. Therefore, support from the public and businesses in Indonesia is needed to increase public awareness of the importance of halal certificates. Furthermore, while there are challenges in harmonizing domestic policies with international standards, international law offers immense opportunities. With an inclusive and collaborative approach, OIC countries can capitalize on these opportunities to achieve a sustainable and inclusive Islamic economic equilibrium. Support from international and regional organizations is crucial in strengthening the capacity of OIC countries to implement international law effectively.